2016
DOI: 10.5588/ijtld.15.0889
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and 8-year follow-up of an uninterrupted oxygen supply system in a hospital in The Gambia

Abstract: SUMMARYSETTING: A 42-bed hospital operated by the Medical Research Council (MRC) Unit in The Gambia.OBJECTIVE: To devise, test and evaluate a cost-efficient uninterrupted oxygen system in the MRC Hospital.DESIGN: Oxygen cylinders were replaced with oxygen concentrators as the primary source of oxygen. An uninterruptable power supply (UPS) ensured continuity of power. Hospital staff were trained on the use of the new system. Eight years post-installation, an analysis of concentrator maintenance needs and costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
(24 reference statements)
0
36
0
Order By: Relevance
“…Where pulse oximeters were used, they were valued as both a diagnostic aid (determining which children require oxygen therapy) and therapeutic aid (giving staff and patients confidence in oxygen therapy; Gray et al) 3 , 49 , 52 , 56 . Limited data suggested that the introduction of pulse oximetry can improve oxygen use and reduce pneumonia case fatality rates, even with suboptimal oxygen access 3 , 56 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Where pulse oximeters were used, they were valued as both a diagnostic aid (determining which children require oxygen therapy) and therapeutic aid (giving staff and patients confidence in oxygen therapy; Gray et al) 3 , 49 , 52 , 56 . Limited data suggested that the introduction of pulse oximetry can improve oxygen use and reduce pneumonia case fatality rates, even with suboptimal oxygen access 3 , 56 …”
Section: Resultsmentioning
confidence: 99%
“…less than daily) and brief (e.g. less than 20 minutes), but not if power failures are frequent or prolonged 49 . Solar power with battery storage is feasible, but requires experienced technicians and quality products 26 , 30 , 31 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also require technical maintenance including regular filter changes. Not all models of oxygen concentrators are technically suitable for sustained use in a tropical environment [75]. Centralized, piped oxygen systems typically deliver pressurized oxygen through wall outlets to bed spaces in the ICU.…”
Section: Oxygenmentioning
confidence: 99%